Dimensions of communication: Malaysian experience - Osman, Mohd. Nizam (Universiti Putra Malaysia Press, 2008)
Rapid advances in communication technologies, especially through the technological advances made in the fields of computing and telecommunication technologies may have a significant impact on the dimensions of communication, at the interpersonal, social, political and economic levels.